2014
DOI: 10.3390/su6095876
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Density in an Uneven City, Santiago de Chile: Implications for Social and Environmental Sustainability

Abstract: Efforts to promote infill development and to raise densities are growing in many cities around the world as a way to encourage urban sustainability. However, in cities polarized along socio-economic lines, the benefits of densification are not so evident. The aim of this paper is to discuss some of the contradictions of densification in Santiago de Chile, a city characterized by socio-spatial disparities. To that end, we first use regression analysis to explain differences in density rates within the city. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…This social group is limited in power, capital and wealth. Such findings accord with prior studies that acknowledge less green space cover as a good indication of lower socioeconomic status of the residential areas in Johannesburg of South Africa (Sch€ affler & Swilling, 2013), Delhi of India (Gupta et al, 2012), Milwaukee of USA (Heynen, Perkins, & Roy, 2006), Santiago of Chile (Aquino & Gainza, 2014), Berlin of Germany (Kabisch & Haase, 2014), Brisbane of Australia (Shanahan et al, 2014) and cities of UK (Dempsey, Brown, & Bramley, 2012;Pauleit, Ennos & Golding, 2005). The quality index is negatively correlated with the income variable, housing variables and percentage of float population, but is insignificantly related with the occupation and education variables.…”
Section: Spatial Regressionsupporting
confidence: 92%
See 1 more Smart Citation
“…This social group is limited in power, capital and wealth. Such findings accord with prior studies that acknowledge less green space cover as a good indication of lower socioeconomic status of the residential areas in Johannesburg of South Africa (Sch€ affler & Swilling, 2013), Delhi of India (Gupta et al, 2012), Milwaukee of USA (Heynen, Perkins, & Roy, 2006), Santiago of Chile (Aquino & Gainza, 2014), Berlin of Germany (Kabisch & Haase, 2014), Brisbane of Australia (Shanahan et al, 2014) and cities of UK (Dempsey, Brown, & Bramley, 2012;Pauleit, Ennos & Golding, 2005). The quality index is negatively correlated with the income variable, housing variables and percentage of float population, but is insignificantly related with the occupation and education variables.…”
Section: Spatial Regressionsupporting
confidence: 92%
“…The scale (district in particular) of analysis differ from that in other studies. For example, previous studies analyze the PGSs provision at community, walking distance, and census scales (Aquino & Gainza, 2014;Dempsey et al, 2012;Kabisch & Haase, 2014;Pauleit et al, 2005;Shanahan et al, 2014). Given the growing body of literature on the neighborhood sociodemographics and PGSs provision, further studies can compare the correlations at different scales among different cities and analyze the policy and social contributors to these relationships.…”
Section: Binarymentioning
confidence: 97%
“…Numerous studies have examined the accessibility and usability of urban parks in developed and developing countries [38,[46][47][48][49][50]. Many studies have demonstrated that the distribution of green spaces is often related to the geographical locations and the development history in the urban area [51][52][53][54][55]. These studies, however, failed to link the characteristics of the parks and the urban residents.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely claimed that compact urban form promotes social life and liveability within the public urban areas and outdoor spaces, and thus enhances social sustainability of communities. These claims include higher sense of safety, intense social interactions, frequent outdoor exchange, reduced social segregation, higher feeling of environmental quality, and lower violence, to name but a few (Jenks 2017;Aquino and Gainza 2014;Raman 2010;Jacobs 2000). However, scholars call for more scientific investigations and empirical evidence from across the globe in order to gain a fine-tuned understanding from the relationship between compact urban form and urban social sustainability (Jenks 2009;Burgess 2000).…”
Section: Introductionmentioning
confidence: 99%